Efficient Detection of Pathogenic Leptospires Using 16S Ribosomal RNA. - Backstedt, Brian T. (2015)
University of Maryland. College Park. Department of Veterinary Medicine and Virginia-Maryland Regional College of Veterinary Medicine. Maryland, USA